PERBEDAAN ANTIKOAGULAN EDTA DAN HEPARIN TERHADAP NILAI HEMATOKRIT - rahmatullah, widia; B. Labito, Rahmin; Aini, Resmi; Azimata R, Rudina; Handayani, Reska (STIKES Syedza Saintika Padang, 2023)
Hematocrit examination is one of the examinations to determine the volume of erythrocytes contained in the blood. Determination of the hematocrit value can be done by the microhematocrit method, using a sample of venous blood mixed with an anticoagulant. Anticoagulant Ethylene Diamine Tetra Acetate (EDTA) can bind calcium ions (Ca) so that clotting does not occur but the use of inappropriate concentrations and volumes of EDTA anticoagulants can cause low hemoglobin levels as well as hematocrit values. Heparin anticoagulants can inhibit the conversion of prothrombin into thrombin, but if used incorrectly it causes cells to agglomerate resulting in invalid calculations. This study aims to determine the average and differences in hematocrit values using EDTA and heparin anticoagulants. This type of research is descriptive analytic which is a research method that functions to describe an object under study. The research analysis used univariate analysis to obtain the average hematocrit value and bivariate analysis used the Independent T-test to determine differences in the results of the hematocrit values using EDTA anticoagulants and heparin anticoagulants. The results of the examination of the hematocrit value of the average EDTA anticoagulant were 38.49% while the average Heparin anticoagulant hematocrit value was 40.05%. Difference in the average value of hematocrit is 1.56%. The results of the Independent T-test statistic where the p value > 0.05 is sig 0.205, which means that the Ho hypothesis is accepted. So it can be concluded that there is no significant difference between the hematocrit values using EDTA and heparin anticoagulants.